Twisted : a pretty little liars novel - Shepard, Sara, 1977- (New York : Harperteen, 2011)
Even though the disappearance of Alison DiLaurentis has been solved, Spencer, Emily, Hanna and Aria harbor other secrets which could interfere with their perfect lives, as they try to forget what happened to them in Jamaica last spring.
Keywords: Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Mystery fiction